Acute cardiogenic shock secondary to blunt traumatic aortic valve injury - Eric N. Quintana; Alexandra DeBose-Scarlett; Thomas A. McLaren; Stephen P. Gondek; Michael C. Smith; Madeleine R. Alder; Michael T. Baker; Ashish S. Shah; Tarek S. Absi (Trauma Case Reports)
Background: Blunt cardiac injuries rarely result in aortic valve cusp rupture, leading to acute aortic insufficiency and cardiogenic shock. This rare clinical entity carries a high mortality rate if left undiagnosed and not managed surgically, with few patients surviving beyond 24 h. It presents a diagnostic challenge in the polytrauma patient in shock, with multiple possible and complementary etiologies. Case presentation: We present a 56-year-old male with persistent hypotension, a wide pulse pressure, and elevated serum troponin levels suggesting blunt cardiac injury after a motor vehicle accident. Transthoracic and transesophageal echocardiography revealed normal biventricular function but severe aortic insufficiency due to prolapse of the left coronary cusp.He was taken emergently to surgery, where aortic valve exploration revealed complete left coronary cusp avulsion from the aortic annulus with a mid-cusp tear, requiring aortic valve replacement with a bioprosthetic valve. Postoperative echocardiography showed normal biventricular function with a well-seated bioprosthetic aortic valve with no insufficiency. Conclusions: Traumatic aortic valve injury can lead to torn or prolapsed cusps causing acute aortic insufficiency leading to cardiogenic shock, but early recognition with appropriate and targeted diagnostic imaging is vital to prevent rapid patient deterioration and demise.